Conceptual Foundations Of Artificial Intelligence - Gacem Hadda; Aouane Azeddine (جامعة الوادي University of Eloued, 2024)
This paper seeks to chart the conceptual framework of artificial intelligence (AI), encompassing an exploration of its historical genesis, definitional parameters, methodological approaches, and domain-specific applications, while also examining the significant implications, inherent risks, and challenges that accompany its adoption. The analysis highlights the pivotal role of AI in revolutionizing both theoretical paradigms and practical methodologies, enabling the emulation of human cognitive processes within digital infrastructures. Prominent applications such as expert systems, neural networks, genetic algorithms, and fuzzy logic illustrate the breadth and depth of AI's impact
Keywords: Artificial Intelligence; AI Applications